Volatility spillovers in the Thai palm oil market - Songsiengchai, Patchaya; Sidique, Shaufique Fahmi; Djama, Marcel; Hook, Law Siong (American Scientific Publishers, 2018)
This paper investigates the effect of global prices in the Thai palm oil market. We provide comprehensive evidence of growth and volatility spillovers for the key crop, crude palm oil in Thailand over the period 1996 to 2015. The Dynamic Conditional Correlation model (DCC) and Granger Causality tests are used, to analyze price volatility effects among Thai and Malaysian crude palm oil and World crude oil prices. Our findings delivered several significant conclusions; that higher prices indicates a positive impact on their uncertainty and also increase a correlation variance among them. Moreover, the Malaysian crude palm oil and world crude oil returns have spillover effects on each of their uncertainty, while Malaysian crude palm oil return has a strong effect on the Thai crude palm oil price and vice versa. Therefore, the government and policy makers in Thailand should pay heed to the changes and fluctuations in those global prices.